Global Saddles for Planar Maps - Alarcón, B (2016)
We study the dynamics of planar diffeomorphisms having a unique fixed point that is a hyperbolic local saddle. We obtain sufficient conditions under which the fixed point is a global saddle. We also address the special case of (Formula presented.)-symmetric maps, for which we obtain a similar result for (Formula presented.) homeomorphisms. Some applications to differential equations are also given. © 2016 Springer Science+Business Media New York